Regional Distribution of Creative and Cultural Industries in Indonesia - Fikri Zul Fahmi (European Regional Science Association (ERSA), 2015)
This study examines the degree to which creative industries fit regional economic settings in the developing world. In so doing, we examine the characteristics of regions where clusters of these industries are found, particularly in Indonesia. Our findings show that creative industries develop in particular regions in this country, but the characteristics of these industries and spatial settings are different from developed countries. In the literature, it is well-established that creative industries are most likely to concentrate in large urban regions, where innovation and cross-fertilization of ideas take place with the support of talent pooling and relatedness among niche producers. This argument is valid for explaining the clustering of ?innovative? creative industries in Indonesia. However, the same conclusion cannot be drawn for long-established ?traditional? cultural industries, which are promoted as creative industries by the government, although they rather focus on preserving heritage values. In this respect, we suggest that policy strategies for creative industries would be applicable to fairly advanced regions with sufficient human capital and economic diversification. Meanwhile, regions specialized in traditional cultural industries can apply a different strategy to optimize the impact of these industries.
Keywords: R10; R12; Z11; Z18; 330; creative industries; cultural industries; regional distribution; Indonesia